2018
DOI: 10.3390/molecules23092392
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Infected Wounds

Abstract: The treatment of skin wounds is a key research domain owing to the important functional and aesthetic role of this tissue. When the skin is impaired, bacteria can soon infiltrate into underlying tissues which can lead to life-threatening infections. Consequently, effective treatments are necessary to deal with such pathological conditions. Recently, wound dressings loaded with antimicrobial agents have emerged as viable options to reduce wound bacterial colonization and infection, in order to improve the heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
410
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(424 citation statements)
references
References 168 publications
2
410
0
12
Order By: Relevance
“…According to the results of Table 1 and Figure 12, coated scaffolds (sample B) against E. coli appear to have superior antibacterial effects in comparison with S. aureus after 24h. This is in consistent with the findings of our previous study [36] as well as results reported in other studies [43][44][45]. It seems that the high hydrophilicity of Gram-negative bacteria in comparison with Gram-positive species renders them more susceptible to the membrane damage via chitosan cations.…”
Section: Discussionsupporting
confidence: 93%
“…According to the results of Table 1 and Figure 12, coated scaffolds (sample B) against E. coli appear to have superior antibacterial effects in comparison with S. aureus after 24h. This is in consistent with the findings of our previous study [36] as well as results reported in other studies [43][44][45]. It seems that the high hydrophilicity of Gram-negative bacteria in comparison with Gram-positive species renders them more susceptible to the membrane damage via chitosan cations.…”
Section: Discussionsupporting
confidence: 93%
“…S. aureus biofilms rarely resolve with antibiotic treatment alone and usually require surgical intervention (debridement, drainage, incision) 35 . Many antibiotics reduce bacterial burdens within biofilms but eradication represents an arduous challenge even in vitro 5,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Modern dressings are capable of both maintaining this moist wound environment and providing a physical barrier between the wound and contamination from the external environment [4,29]. Therapeutic outcomes and wound response to drugs can also be improved when dressings are fully dissolvable, non-replaceable, or non-adherent and if they distribute treatments (e.g., components that can help in the removal of necrotic tissues, prevent/treat infections, or both) to the wound site in a precise manner [88]. Wound dressings are, today, functionalized to incorporate several classes of antibiotics (e.g., quinolones, tetracyclines, aminoglycosides, cephalosporins) or other substances with antibacterial properties (e.g., essential oils) delivered directly at the wound sites [88].…”
Section: Non-phage-based Wound Treatmentsmentioning
confidence: 99%
“…Therapeutic outcomes and wound response to drugs can also be improved when dressings are fully dissolvable, non-replaceable, or non-adherent and if they distribute treatments (e.g., components that can help in the removal of necrotic tissues, prevent/treat infections, or both) to the wound site in a precise manner [88]. Wound dressings are, today, functionalized to incorporate several classes of antibiotics (e.g., quinolones, tetracyclines, aminoglycosides, cephalosporins) or other substances with antibacterial properties (e.g., essential oils) delivered directly at the wound sites [88]. The recruitment of cells, stimulation of cell proliferation, and regulation of extracellular matrix deposition can all be achieved using growth factors [4].…”
Section: Non-phage-based Wound Treatmentsmentioning
confidence: 99%